A Mobile-Based High Sensitivity On-Field Organophosphorus Compounds Detecting System for IoT-Based Food Safety Tracking. (20th February 2017) - Jin, Han; Qin, Yajie; Liang, Hao; Wan, Lei; Lan, Hao; Chen, Guoping; Liu, Ran; Zheng, Li-rong; Chiang, Patrick; Hong, Zhi-liang
Abstract : A mobile-based high sensitivity absorptiometer is presented to detect organophosphorus (OP) compounds for Internet-of-Things based food safety tracking. This instrument consists of a customized sensor front-end chip, LED-based light source, low power wireless link, and coin battery, along with a sample holder packaged in a recycled format. The sensor front-end integrates optical sensor, capacitive transimpedance amplifier, and a folded-reference pulse width modulator in a single chip fabricated in a 0.18  μ m 1-poly 5-metal CMOS process and has input optical power dynamic range of 71 dB, sensitivity of 3.6 nW/cm 2 (0.77 pA), and power consumption of 14.5  μ W. Enabled by this high sensitivity sensor front-end chip, the proposed absorptiometer has a small size of 96 cm 3, with features including on-field detection and wireless communication with a mobile. OP compound detection experiments of the handheld system demonstrate a limit of detection (LOD) of 0.4  μ mol/L, comparable to that of a commercial spectrophotometer. Meanwhile, an android-based application (APP) is presented which makes the absorptiometer access to the Internet-of-Things (IoT).